The Relationship between Compulsive Sexual Behavior, Religiosity, and Moral Disapproval. Issue 3 (3rd April 2023) - Coleman, Eli; Jennings, Todd; Gleason, Neil; Danielson, Samuel; Nielsen, Katja H.; Miner, Michael H.; Rahm-Knigge, Ryan L.
Abstract: Compulsive sexual behavior (CSB) is associated with religiosity and moral disapproval for sexual behaviors, and religiosity and moral disapproval are often used interchangeably in understanding moral incongruence. The present study expands prior research by examining relationships between several religious orientations and CSB and testing how moral disapproval contributes to these relationships via mediation analysis. Results indicated that religious orientations reflecting commitment to beliefs and rigidity in adhering to beliefs predicted greater CSB. Additionally, moral disapproval mediated relationships between several religiosity orientations and CSB. Overall, findings suggest that religiosity and moral disapproval are related constructs that aid in understanding CSB presentations.